Study of the rare decay J/ψ → μ + μ − μ + μ − - The LHCb collaboration; R. Aaij; A. S. W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A. A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C. A. Aidala; et al. (Journal of High Energy Physics)
Abstract The rare electromagnetic J/ψ → μ + μ − μ + μ − decay is observed with a significance greatly exceeding the discovery threshold, using proton-proton collision data collected by the LHCb experiment during 2016–2018 at a center-of-mass energy of 13 TeV, corresponding to an integrated luminosity of 5.4 fb −1. The rate of this decay is measured relative to that of the J/ψ → μ + μ − mode. Using the QED model for the four-muon decay in the efficiency estimation, its branching fraction is determined to be B J / ψ → μ + μ − μ + μ − = 1.13 ± 0.10 ± 0.05 ± 0.01 × 10 − 6 , $$ \mathcal{B}\left(J/\psi \to {\mu}^{+}{\mu}^{-}{\mu}^{+}{\mu}^{-}\right)=\left(1.13\pm 0.10\pm 0.05\pm 0.01\right)\times {10}^{-6}, $$ where the uncertainties are statistical, systematic and due to the uncertainty on the branching fraction of the J/ψ → μ + μ − decay.